Early and Midterm Outcomes of Valve-Sparing Aortic Root Replacement—Reimplantation Technique - Cevasco, Marisa; McGurk, Siobhan; Yammine, Maroun; Sharma, Lokesh; Ejiofor, Julius; Norman, Anthony; Singh, Michael N.; Shekar, Prem (AORTA, 2018)
Background Valve-sparing aortic root replacement (VSARR) is an increasingly popular alternative to traditional aortic root replacement for aortic root aneurysm disease with a normal aortic valve. We evaluated the early and midterm outcomes of VSARR—reimplantation technique (VSARR-RT) done at a single institution over a decade.Materials and Methods We performed a retrospective study of all patients who underwent VSARR-RT between January 2004 and July 2014.Results A total of 85 patients underwent VSARR-RT. Median time to latest echocardiographic follow-up was 4 years (range: 15–72 months). Total observation time was 491 patient years. Mean age was 44.6 ± 14.3 years, and 13 (15%) were women. Thirty-nine (46%) patients had a connective tissue disorder and 6 (7%) had a bicuspid aortic valve. Thirty-three (39%) patients underwent concomitant procedures, including coronary artery bypass grafting (n = 9, 11%), mitral valve repair (n = 8, 9%), and aortic hemi-arch replacement (n = 7, 8%). There were no operative deaths or in-house mortality and no postoperative strokes. Kaplan-Meier analysis demonstrated survival of 99% (95% confidence interval [CI]: 97–100%) at 2 years and 98% (95% CI: 97–100%) at 8 years. Freedom from reoperation was 95.8% (95% CI: 91.2–100%) at 8 years. Freedom from endocarditis was 100% at 8 years. At the last echocardiographic follow-up, 95% of patients were free of severe aortic regurgitation (AR) and 82% free of moderate AR. Of the four patients who had severe AR, three underwent reoperations and received prosthetic valves and one is being clinically monitored.Conclusion This study reports early and midterm outcomes after VSARR-RT at our institution, including those patients who underwent a VSARR-RT procedure combined with other procedures. Further follow-up remains necessary to determine long-term outcomes.
Keywords: valve-sparing aortic root replacement; David procedure; reimplantation technique